29Si and 27Al NMR study of the structural transformation of calcined kaolin residue-based geopolymer using low alkali activator content for sustainable construction materials. (1st July 2023) - Prasanphan, Sitthisak; Hemra, Khanthima; Wannagon, Anucha; Kobayashi, Takaomi; Onutai, Sujitra; Jiemsirilers, Sirithan
Abstract: Geopolymer commercialization efforts in parallel with unconventional research are the only pathway to achieve the large-scale deployment of geopolymer technology. Geopolymers with a low quantity of alkali activator produced by the compression process are one way to bring this technology to industry because of the higher strength and lower efflorescence of the product. In this work, calcined kaolin residue-based geopolymers with a low alkali activator content were synthesized by various Si/Al mole ratios with soluble silicate from Na2 SiO3 to adjust the Si ratio. The effects of Si/Al mole ratios on the structural transformation, microstructure, and compressive strength of geopolymers containing low alkali activator content were studied. The structural transformation and microstructure of geopolymers were characterized by NMR, SEM, and BET, and the compressive strength was assessed using a mechanical testing machine. The results present that geopolymer synthesized with various Si/Al mole ratios of precursor materials impacted the change in polymerization degree of silicate species (Q n ( m Al)) and aluminate species. The Q 4 (4Al) and Q 4 (3Al) structures were transformed into the Q 4 (2Al) structure, and the content of the Al IV structure decreased when the Si/Al mole ratio of geopolymer was increased to 1.58. However, the contents of Q 4 (4Al) and Al IV structures increased again when the geopolymer had a Si/Al mole ratio of 1.62. SEM/EDX and BET results of geopolymers presented denser matrices, more amorphous aluminosilicate gels, and higher Si/Al ratios in aluminosilicate gels, while the pore size and pore volume were quite small when the Si/Al mole ratio of precursor materials was increased. In contrast, the highest Si/Al mole ratio of 1.62 showed different properties. The compressive strength of geopolymer was maximized at a Si/Al mole ratio of 1.58, and the decline in compressive strength of geopolymer with higher Si/Al mole ratio was related to the contents of Si–O–Si, Si–O–Al, and Al–O–Al bonds, content of aluminosilicate gels, and properties of the microstructure. The geopolymer synthesis using calcined kaolin residue and low alkali activator content is considered an eco–friendly process, which uses waste materials and less chemicals, and obtains high-strength products. Graphical abstract: Image 1 Highlights: Structure of geopolymers with low alkali activator content and various Si/Al mole ratios was studied by 29 Si and 27 Al NMR. TransFormation of Q 4 (4Al) and Q 4 (3Al) into more polymerized Q 4 (2Al) has been confirmed. Al V and Al VI sites were mainly transformed as Al IV sites during the geopolymerization reaction. Geopolymer synthesized with higher Si/Al mol ratios showed dense microstructure and more aluminosilicate gels. An increasing of the compressive strength was related to structural transformation, dense microstructure, and pore size of the geopolymer.